Design and Manufacturing of Soybean Epidermis Peeler Machine - Romiyadi Romiyadi; Yudi Dwianda (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2019)
The soybean epidermis peeler machine was a machine used to peel of soybean epidermis from the soybean. The purpose of the study was to design and manufacture of soybean epidermis peeler machine with a capacity of 3 kg for a process. In this study, the soybean epidermis peeler machine was designed and manufactured with uses 2 shaft to peel the soybean epidermis from the soybean. From the process of designing and manufacturing, has produced a soybean epidermis peeler machine with a capacity of 3 kg for a process. The machine uses a electric motor with a power of 0.5 HP. The transmission system uses pulley transmission between electric motor with 1st shaft and uses sprocket and gear transmission between 1st shaft and 2nd shaft.